Nutritional, Energy and Sanitary Aspects of Swine Manure and Carcass Co-digestion - Tápparo, Deisi Cristina; Rogovski, Paula; Cadamuro, Rafael Dorighello; Marques Souza, Doris Sobral; Bonatto, Charline; Frumi Camargo, Aline; Scapini, Thamarys; Stefanski, Fábio; Amaral, André; Kunz, Airton; Hernández, Marta; Treichel, Helen; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Renewable energy can assist the management of the effects of population growth and rapid economic development on the sustainability of animal husbandry. The primary aim of renewable energy is to minimize the use of fossil fuels via the creation of environmentally friendly energy products from depleted fossil fuels. Digesters that treat swine manure are extensively used in treatment systems; and inclusion of swine carcasses can increase the organic loading rate thereby improving biogas yield and productivity on farms. However, the characteristics of the components including animal residues, proteins, lipids, remains of undigested feed items, antimicrobial drug residues, pathogenic microorganisms and nutrient contents, are complex and diverse. It is therefore necessary to manage the anaerobic process stability and digestate purification for subsequent use as fertilizer. Efficient methane recovery from residues rich in lipids is difficult because such residues are only slowly biodegradable. Pretreatment can promote solubilization of lipids and accelerate anaerobic digestion, and pretreatments can process the swine carcass before its introduction onto biodigesters. This review presents an overview of the anaerobic digestion of swine manure and carcasses. We analyze the characteristics of these residues, and we identify strategies to enhance biogas yield and process stability. We consider energy potential, co-digestion of swine manure and carcasses, physical, chemical, and biological pretreatment of biomass, sanitary aspects of swine manure and co-digestates and their recycling as fertilizers.